PEMBENTUKAN KARAKTER SPIRITUAL PESERTA DIDIK MELALUI KURIKULUM INTEGRATIF DI PONDOK PESANTREN MODERN AL MA - Shofa Fauziah; Irawan Irawan; Rohmat Mulyana Sapdi (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study examines the implementation of an integrative curriculum in shaping students' spiritual character at Modern Islamic Boarding School (Pesantren) Al Ma'soem, Bandung. The background of this research is the persistent dichotomy between religious and general sciences in Islamic education, which often weakens the internalization of spiritual values. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis involving curriculum leaders, teachers, and students. The findings reveal that the integrative curriculum at Al Ma'soem is implemented by unifying the national curriculum and pesantren curriculum within a value-based educational framework grounded in the Qur'an and Sunnah. Spiritual values are integrated into academic learning, daily religious practices, and the boarding school culture. The results indicate positive changes in students' spiritual awareness, discipline in worship, moral responsibility, and their ability to perceive learning activities as part of worship. The discussion shows that the success of the integrative curriculum is strongly supported by structured spiritual habituation, teacher exemplarity, and value-based leadership. In conclusion, the integrative curriculum contributes significantly to the development of students' spiritual character and offers an effective model for Islamic educational institutions in responding to contemporary educational challenges while maintaining their religious identity.